2011
DOI: 10.1007/s12017-011-8147-9
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Microglial Markers in Alzheimer’s Disease: Elevated Chitotriosidase Activity but Lack of Diagnostic Utility

Abstract: Activated microglial cells, which are the resident macrophages of the central nervous system, surround amyloid β-plaques in Alzheimer's disease (AD) brains. Inflammation including microglial activation may contribute in AD pathogenesis, and biomarkers for this process may thus be of value to study AD pathogenesis and might facilitate development of therapies targeting these cells. We therefore examined cerebrospinal fluid (CSF) biomarkers in patients with AD, other dementias, mild cognitive impairment and in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 42 publications
10
71
1
1
Order By: Relevance
“…2b). The different associations for YKL-40 and CCL2 are consistent with a previous report from our laboratory [41], where YKL-40 and CCL2 did not correlate in healthy controls or AD patients, although they correlated in patients with other dementias. There are several possible explanations for these differences in associations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…2b). The different associations for YKL-40 and CCL2 are consistent with a previous report from our laboratory [41], where YKL-40 and CCL2 did not correlate in healthy controls or AD patients, although they correlated in patients with other dementias. There are several possible explanations for these differences in associations.…”
Section: Discussionsupporting
confidence: 92%
“…However, CCL2 results in AD are conflicting; one study showed increased CSF levels in AD [40], but another could not replicate this finding [41]. We could not find any association between CCL2 and age, or differences between DS and controls.…”
Section: Discussioncontrasting
confidence: 57%
“…In human brain, it is suggested that ChT is synthesized by microglia [16] and it has been reported that high CSF ChT levels in several neurological conditions including multiple sclerosis, acute ischemic stroke, and Alzheimer's disease (AD) [12][13][14][15]36]. This evidence suggests the overproduction of this enzyme exerts a deleterious effect in many degenerative disorders [15,[37][38][39][40]. Regarding ALS, some studies have previously shown an increased blood ChT activity suggesting this enzyme as a potential biomarker [29], and elevated ChT levels in ALS-CSF proposing a role for the enzyme in the disease pathogenesis [16,18].…”
Section: Discussionmentioning
confidence: 99%
“…In the human brain, ChT is proposed to be synthesized by microglia and high CSF ChT levels have been shown in several neurological conditions [14][15][16]. Previous reports revealed that ChT is increased in CSF in patients with ALS and proposed this enzyme as a potential biomarker for ALS [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…moulds (Lee et al, 2008), exert numerous other effects in the mammalian host, including pathological conditions such as autoimmune, neurological or lysosomal storage diseases in humans (Brinkman et al, 2005;Boot et al, 1999;Bussink et al, 2006;Di Rosa et al, 2006;Lautner et al, 2011;Lee et al, 2011Lee et al, , 2012Mattsson et al, 2011;Sotgiu et al, 2008;Verbeek et al, 2010) and crystalline pneumonia in mice (Hoenerhoff et al, 2006;Liu et al, 2009). It will be of interest to examine such biologically relevant activities of mammalian chitinases and chitolectins in order to improve the understanding of the roles of similar proteins from bacterial pathogens.…”
Section: R F Frederiksen and Othersmentioning
confidence: 99%